Integrated Technology for Classroom Management Strategies in a Computer-Assisted Language Learning - Christian Bernard Nichols Djami (Gemilang Maju Publikasi Ilmiah (GMPI), 2022)
This study was carried out to investigate the integrated technology in Computer-Assisted Language Learning (CALL) class support classroom management strategies. The study employed mixed-methods and involved 27 students and a lecturer of a CALL class in an English Language Education Study Program. The data collection instruments were a questionnaire, interview guide, and observation notes. The data analysis was processed using descriptive statistics, particularly for the questionnaire results. Meanwhile qualitative analyses were conducted to process the interview results and observation notes. The results of the study showed that necessary relevant technology was integrated in the CALL class and it could support classroom management strategies by engaging students in learning, delivering materials efficiently, and creating an immersive learning environment using gamification through internet. Using computer to support learning is effective to create an immersive environment and to manage classroom. The use of computer in language learning is able to support classroom management for a lecturer inside or outside the classroom.